A referenciação nos textos do gênero carta pessoal produzidos por alunos da Educação de Jovens e Adultos - Santos, Miriã Soares dos (2015)
This research aims to analyze the referential process in personal letters written by students of the Youth and Adult Education (EJA) from two schools of the city of Guarulhos. From a universe of forty letters, we selected thirteen letters, which is the corpus of this dissertation. The theoretical basis of this study takes into account the Text Linguistics and the main authors in this field, such as Mondada & Dubois, Beaugrande, Teun van Dijk, Luiz Antonio Marcuschi, Jean Michel Adam, Cavalcante and Lima, Lima and Feltes, Apothelóz, Schwarz-Friesel, Morato, Koch, Elias, among others, referring to concepts of text and context, referential progression, frames, referents as discourse objects, and indirect anaphora. We also based our analyses in Bakhtin, with regard to the studies of genres. Studies on the referents are in the current agenda of the Text Linguistics and bring new perspectives to work with texts, as regards the production and comprehension. Specifically, we have analyzed the indirect anaphora as a phenomenon for the coherence construction and text progression, based in socio-cognitive context of the interlocutors in order to establish associations and / or inferences to keep the textual progression and for the construction of coherence. We seek to explore in this study mainly mental representations expressed in the texts that guarantee the textual progression through the adoption of two categories of analysis: Introduction of anchored and non-anchored referents, and Recategorisation of referents through reconstruction / reactivation , blurring / deactivation and packaging and labeling. The results showed that the texts produced by students of EJA are consistent and indirect anaphora ensured coherence and textual progression